Design and Performance Analysis of a Sub-micron Piezoelectric Flexible Micro Drive System - Zhang Chuanwei; Li Niuniu; Yang Manzhi; Guo Wei; Xu Kejun; Ge Hongyu (Jixie chuandong)
In order to get the precision linear motion output，a piezoelectric flexible micro drive system that composed of piezoelectric actuators and flexible micro mechanism is designed，and the system has sub-micron positioning accuracy driven by piezoelectric actuator. A kind of precise flexible micro mechanism is designed based on the principle of flexible hinge guide and transmission，and on this basis， a design scheme of piezoelectric flexible micro drive system is proposed. The kinematics analysis，strength analysis and dynamic analysis of the system are accomplished by the finite element method. The analysis results show that the system has the advantages such as high positioning accuracy which the maximum positioning error is 0.24 μm，good strength performance and excellent dynamic performance. This study has a certain reference value for the research and application of micro drive system.